TINGKAT PENGETAHUAN IBU TENTANG IMUNISASI DASAR PADA BAYI USIA 0-12 BULAN DI PUSKESMAS PEKAUMAN BANJARMASIN - Noverda Ayuchecaria; novia Ariani (Jurnal Insan Farmasi Indonesia, 2019)
The completeness of basic immunization needs to be considered by parents, especially mothers who generally bring their children to immunization in the puskesmas or posyandu. The level of knowledge of a mother is very influential on the success of complete immunization. Knowledge and awareness of the importance of immunization for children can increase the success of immunization programs. The purpose of this study was to determine the level of knowledge of a mother about basic immunization at the Pekauman Health Center. The type of research is Non-experimental research that is observational. The instrument used was a questionnaire sheet that had been tested for validity and reliability first. Pupolation used is the mother who brought her child and came during immunization to the Pekauman Health Center for the period of April and May 2019. The samples used with consecutive random sampling method, namely 110 mothers. Data analysis was done by making a percentage of each item statement and data then presented descriptively. The results of this study from 110 mothers showed that mothers had a good level of knowledge of 46.36% (51 mothers), sufficient level of knowledge of 55.82% (57 mothers) and a low level of knowledge of 1.82% (2 mothers).